Entre cangaceiros e lobisomens: a produção de medo em abordagens de assalto com domínio de cidades - Rocha, Claudio Renan Gadelha (2024)
Through the perspective of victims of the assaults on financial institutions with domains in cities that took place in Aracati (CE), Araçatuba (SP) and Guarapuava (PR), the efforts of this research seek the consequences of these events in cities and in people's lives who were directly or indirectly victimized by them. Initially, a literary review was carried out on the production of fear in History and Literature to understand what a sociological investigation can reveal about this emotion. The research was developed through conversations with witnesses of the crimes about their feelings of security in the city and the actions of the police before the robberies. Then, episodes of infotainment programs that are famous on Brazilian television and comments from channels and relevant figures were reported virtually with the aim of investigating the way in which information about these crimes is shared. The investigation calls lycanthropy the process encouraged by the media that alters the real dimensions of robbers through the creation of narratives that distort their origin and motivation. The work argues that the absence of a process that ends the cycle of production and reproduction of fear can cause social damage, since this scenario, when instigated and manipulated by different social agents, can be proliferated or intensified in an indefinite way within the cities.